Human Resource Management of the Indonesian Armed Forces Special Operations Command in Developing Counterterrorism Capabilities - Agus Adriyanto; Fauzia Gustarina Cempaka Timur (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Indonesian Armed Forces Joint Special Operations Command (Koopssus TNI) has a strategic role in ensuring national security, especially in situations that require quick and precise action. This study aims to analyze human resource management aspect in the Koopsus TNI in fostering special operations capabilities to deal with the threat of terrorism. This study uses a qualitative approach with a descriptive method. This study uses direct observation and in-depth interviews with the TNI Kooppssus for data collection. The results of the study indicate that fostering special operations capabilities of Koopssus TNI requires a planned, directed, sustainable, and integrated strategy, with a participatory approach that optimizes the involvement of all parties to improve joint capabilities. This strategy includes the formulation, implementation, and evaluation of coaching involving individual training, consolidation, unit training, and inter-unit training arranged in an integrated calendar. These steps support Koopssus TNI in overcoming the threat of terrorism with a focus on intelligence, defense, and regional empowerment. The strategy evaluation shows the need to improve the quality of personnel, training facilities, and resource management to ensure optimal preparedness in dealing with special tasks.